Soziales Entschädigungsrecht Bestand, Grundsätze, Neuordnung - Becker, Ulrich (Studien aus dem Max-Planck-Institut für Sozialrecht und Sozialpolitik, 2018)
"Social compensation law is spread over many, and often obscure, individual laws. It only accounts for a very small part of the social budget and is therefore not a favourite of journalists, politicians and scientists. It only takes the spotlight in very rare cases, such as when catastrophic floods or street riots are in the news. However, social compensation law actually raises elemental issues of governmental liability which are connected to private and public liability law. What distinguishes it from state liability law, which is generally dealt with individually? Why does the state undertake the task of providing for compensation of damages? Why are catastrophes and riots only dealt with ad hoc and by means of individual acts? These questions are answered in three steps: Firstly, by assessing the current state of affairs, which includes fringe areas and international requirements, also from a historical and comparative perspective; secondly, by systematisation, which includes normative ideas on the duty to provide compensation of damages; and thirdly, by reflections on how to organise existing compensation situations, recognise new ones and combine all these by means of codification."